2021
DOI: 10.1002/casp.2588
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and workplace dehumanization at the supermarket: A field study during the COVID‐19 outbreak in Italy

Abstract: This study explores the psychological effects of the COVID‐19 emergency on workers employed in the supermarket sector by analysing their levels of burnout and the relationship between the burnout syndrome and employees' workplace experiences. A sample of 422 Italian workers answered a survey addressing the burnout dimensions (i.e., exhaustion, cynicism, and professional inefficacy) along with perceived organizational factors and dehumanizing representations. Results showed that 32% of the respondents had sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…The findings of this study indicated that first responders experience meta-dehumanization and that such experiences significantly predict burnout. Although the relationship between dehumanization and burnout had been established for other populations (Caesens & Stinglhamber, 2019;Testoni et al, 2022;Valtorta et al, 2021), this is the first study to reveal this link for first responders.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The findings of this study indicated that first responders experience meta-dehumanization and that such experiences significantly predict burnout. Although the relationship between dehumanization and burnout had been established for other populations (Caesens & Stinglhamber, 2019;Testoni et al, 2022;Valtorta et al, 2021), this is the first study to reveal this link for first responders.…”
Section: Discussionmentioning
confidence: 88%
“…This implies that the experience of being dehumanized may contribute to burnout, as do organizational dehumanization (Moriano et al, 2021) and unrealistic expectations (Bagherian & Hosseini, 2019), such as being seen as a superhero (Lanza et al, 2018). Even government employees (Caesens & Stinglhamber, 2019) and private sector employees (Valtorta et al, 2021) have experienced symptoms of burnout in response to dehumanizing experiences at work. More specific to helping professions, Testoni et al (2022) conducted a study of 270 medical professionals dealing with emergency situations and found that dehumanization was linked to higher levels of burnout.…”
Section: Consequences Of Dehumanizationmentioning
confidence: 99%
“…Instagram is a virtual platform, most likely by Romanians, after Facebook. According to Mediafactbook 2021 [11], Instagram users represent 61 % of the online population in Romania, which justifies both the brands and the consumers orientation towards this one. Hence, researching intense interactivity on Instagram during the pandemic provides us with a better comprehension of the new Kaufland communication strategies.…”
Section: Introductionmentioning
confidence: 99%